Improving English Understanding on Computer Software for Class IX Students at SMP Mathla'ul Anwar Tangerang Using the String Method - Alfianah, Yanah; Shelviani, Hanasa; Umami, Sahrul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research improves the understanding of English in class IX students at SMP Mathla'ul Anwar Tangerang through the use of computer software specifically for keyboard shortcut material using the string method (speaking and trying). The method used in this research was Pre-Expermental with a one-shot case study design with data collection using only post-tests, instruments in the form of post-tests as primary data and questionnaires as secondary data which were distributed to 24 students. Data processing was carried out using descriptive quantitative in the form of a descriptive and inferential statistical approach with Minimum Completeness criteria (KKM) as a basis for comparing student test results, besides that the questionnaire was used as a correlation between the use of computer software and the string method (speaking and trying). Validation of the statistical results shows that this method has an influence on improving students' understanding with post-test results above the KKM score and satisfaction scores showing a positive impact on improving English language skills.